(The general geomorphological features and evolution of the western part of the Elazig district, Turkey). - Tonbul, S. (My University, 1987)
The district has been formed as a swell between Malatya depression on the west and Elazig-Uluova depression on the east and in general, it shows a plateau character which has the average elevation of 1300-1400 m. The high parts of both Hasandagi and Bulutlu and Piran mountain chains are seen as two separate erosional surfaces (Pre-Miocene and Lower Miocene surfaces) which have formed from which different levels from one another. -from English summary
Elazig batisinin genel jeomorfolojik ozellikleri ve gelisimi.